Lactate Dehydrogenase Levels after Aortic Valve Replacement: What Do They Tell Us? - Rings, Laura; Mavrova-Risteska, Loreta; Haeussler, Achim; Ntinopoulos, Vasileios; Tanadini, Matteo; Rodriguez Cetina Biefer, Hector; Dzemali, Omer (The Thoracic and Cardiovascular Surgeon, 2024)
Introduction Lactate dehydrogenase (LDH) is a standard postoperative marker for hemolysis in the presence of paravalvular leakage (PVL) after replacement of the aortic valve (AVR). LDH is elevated in certain valves by a fluttering phenomenon. Previous studies suggested a correlation between microparticles (MPs) and LDH elevation after AVR. Thus, we analyze the postoperative relevance of LDH after AVR with transapical transcatheter aortic valves (TA-TAVs) or rapid deployment valves (RDVs).Methods We retrospectively analyzed the data from patients who received an AVR with the RDV and TA-TAV groups between 2015 and 2018. We compared PVL and LDH levels before and after surgery, transvalvular gradients, heart block that required pacemaker implantation, and 30-day mortality.Results In total, 138 consecutive patients were selected for the study: 79 patients in the RDV group (37 Sorin Perceval valve, 42 Edwards Intuity valve) and 59 in the TA-TAV group (Edwards Sapien valve). TA-TAV group was older (median 10 years) and had a higher incidence of PVL (odds ratio 11, 95% confidence interval [CI] 2.5–73.2, p = 0.04)). Interestingly, the TA-TAV group showed lower levels of LDH despite higher rates of PVL. Of note, the Perceval valve trended toward higher LDH values. Additionally, the RDV group showed an increased arrhythmia profile (p = 0.0041); however, the results show lower incidence in pacemaker implantation (95% CI 0.05–1.65, p = 0.635). The 30-day mortality was similar between groups.Conclusion Our data do not support the association between hemolysis and PVL despite elevated LDH in suture-free valves. Our results suggest that LDH could be a marker of extreme heart muscle output or fluttering phenomenon and not a marker of hemolysis after sutureless AVR.
Keywords: aortic valve and root; heart valve surgery; heart valve; transapical; percutaneous (TAVI); cardiac